Dampak Insentif Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada Industri Retail Surabaya - Lilis hidayatus sugiarti; Dea Amellia; Angels Monica; Adinda Diah Fatikha Yusuf; Arinndah Cindy; Agus Wahyudi (https://journal.metanusantara.com/jenius/index.php/jem, 2026)
This study aims to analyze the impact of incentives and work environment on employee job satisfaction in the retail industry in Surabaya. Job satisfaction is a crucial factor influencing employee productivity and retention in retail companies. This study employs a quantitative method with a survey approach. The research population consisted of all permanent employees from three major retail companies in Surabaya, with a sample of 120 respondents selected using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results indicate that incentives have a positive and significant effect on employee job satisfaction (t = 4.512; p < 0.05), and the work environment also has a positive and significant effect on job satisfaction (t = 3.879; p < 0.05). Simultaneously, incentives and work environment significantly affect job satisfaction with F = 28.341 (p < 0.05) and a coefficient of determination (R²) of 0.612, meaning that 61.2% of the variation in job satisfaction can be explained by incentives and work environment. The implication of this study is that retail companies need to design competitive incentive systems and create a conducive work environment to enhance employee job satisfaction.